An unusual compound object in Yamato 793408 (H3.2‐an): The missing link between compound chondrules and macrochondrules?. (5th June 2020) - Barosch, Jens; Hezel, Dominik C.; Marrocchi, Yves; Gurenko, Andrey; Lenting, Christoph
Abstract: We found a large (~2 mm) compound object in the primitive Yamato 793408 (H3.2‐an) chondrite. It consists mostly of microcrystalline material, similar to chondrule mesostasis, that hosts an intact barred olivine (BO) chondrule. The object contains euhedral pyroxene and large individual olivine grains. Some olivine cores are indicative of refractory forsterites with very low Fe‐ and high Ca, Al‐concentrations, although no 16 O enrichment. The entire object is most likely a new and unique type, as no similar compound object has been described so far. We propose that it represents an intermediate stage between compound chondrules and macrochondrules, and formed from the collision between chondrules at low velocities (below 1 m s −1 ) at high temperatures (around 1550 °C). The macrochondrule also trapped and preserved a smaller BO chondrule. This object appears to be the first direct evidence for a genetic link between compound chondrules and macrochondrules. In accordance with previous suggestions and studies, compound chondrules and macrochondrules likely formed by the same mechanism of chondrule collisions, and each represents different formation conditions, such as ambient temperature and collision speed.